Hydrolytic effects of acid and enzymatic pre-treatment on the anaerobic biodegradability of Ascophyllum nodosum and Laminaria digitata species of brown seaweed. (September 2015) - Obata, Oluwatosin; Akunna, Joseph C.; Walker, Graeme
Abstract: Abundant marine biomass in coastal regions has continued to attract increasing attention in recent times as a possible source of renewable energy. This study aimed to evaluate the effects of hydrolytic pre-treatment for the purpose of enhancing biogas yield of Laminaria digitata and Ascophyllum nodosum species found on the west coast of Scotland. Results show that L. digitata, in its natural and untreated form, appears to be more readily hydrolysable than A. nodosum . Two treatments were assessed: acid only and acid followed by enzyme. Both treatments enhanced the hydrolysis of both seaweed species, with acid-enzyme treatment providing a better performance. Highlights: L. digitata and A. nodosum seaweed species are effective biomass for biogas production. L. digitata is more readily hydrolysable than A. nodosum . Combined acid and enzymatic pre-treatment enhances hydrolysis of both seaweed species.